Pregnancy with portal hypertension: a case report - Dhingra, Mansi; Ahmad, Syed Nawaz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Even though pregnancy is rare with cirrhosis and advanced liver disease, it may co-exist in the setting of non- cirrhotic portal hypertension as liver function is preserved. When encountered together it presents a complex clinical dilemma. Physiological hemodynamic changes associated with pregnancy, needed for meeting demands of the growing fetus, worsen the portal hypertension thereby putting mother at risk of potentially life-threatening complications like variceal hemorrhage. Pregnancy also predisposes the patient to develop hepatic decompensation. Thus, management of such cases requires multidisciplinary approach involving obstetricians experienced in dealing with high risk cases, hepatologists, anesthetists and neonatologists. Here through the case report of a 23 year old primigravida with Non Cirrhotic portal hypertension with 33 weeks gestational age in preterm labor we intend to focus upon different aspects of pregnancy with portal hypertension, its complications and management strategies.